A family of solutions related to Shin’s model for probability forecasts - Kizildemir, Melis; Akin, Ertugrul; Alkan, Altug (Walter de Gruyter GmbH, 2024)
Abstract This work develops a family of solutions related to Shin’s model in producing accurate probability forecasts. More precisely, closed-form solutions are derived based on an analytical approach to known solutions and evaluated experimentally for sports betting data sets.